High tech harvest : a look at genetically engineered foods - Marshall, Elizabeth L. (New York : Franklin Watts, 1999)
An overview of recombined DNA technology, or genetic engineering, techniques used to create crop plants and farm animals with characteristics that are attractive to farmers, food processors, and consumers.
Includes bibliographical references (p. 138-140) and index.
Books for the Teen Age (NYPL).
School Library Journal.
Wilson's Junior High School.
Young Adult
Keywords: Agricultural biotechnology -- Juvenile literature; Food -- Biotechnology -- Juvenile literature; Agricultural biotechnology; Food -- Biotechnology; Genetic engineering; Biotechnology; Food; Genetic engineering